PENGEMBANGAN MODEL PEMBELAJARAN PROBLEM SOLVING BERBANTUAN LEARNING MANAGEMENT SYSTEM UNTUK MENGEMBANGKAN KETERAMPILAN BERPIKIR KRITIS SISWA - Titiek Puji Rahayu (Journal of Learning and Technology, 2022)
This study aims to produce a problem solving learning model with LMS in developing students' critical thinking skills on buffer solution material and knowing how to implement it. The research method used is Research & Development (R&D) which refers to the Thiagarajan model with the stages of define, design, and develop. The trial results show that the LMS-assisted problem solving learning model on the buffer solution, make conditions student-centered becomes interactive and fun, improves students' understanding and memory of the buffer solution concept, gives students the freedom to ask questions or express opinions. Based on the research results, it can be concluded that the development of LMS-assisted problem solving learning models can develop students' critical thinking skills on the buffer solution material.